Spermatotoxic Effects of Single-Walled and Multi-Walled Carbon Nanotubes on Male Mice - Farshad, Omid; Heidari, Reza; Zamiri, Mohammad Javad; Retana-Márquez, Socorro; Khalili, Meghdad; Ebrahimi, Melika; Jamshidzadeh, Akram; Ommati, Mohammad Mehdi (Frontiers in Veterinary Science, 2020)
Carbon-based nanomaterials possess a remarkably high potential for biomedical applications due to their physical properties; however, their detrimental effects on reproduction are also concerned. Several reports indicate the toxicity of carbon nanotubes (CNT); nevertheless, their impact on intracellular organelles in the male reproductive organs has not been fully elucidated. Herein, we report on the reprotoxicity of single-walled (SWCNT) and multi-walled carbon nanotubes (MWCN) on several intracellular events and histological criteria in pubertal male BALB/c mice orally treated with 0, 10, and 50 mg/kg/day doses for five weeks. Biomarkers of oxidative stress and mitochondrial functionality, histopathological alterations, and epididymal sperm characteristics were determined. Oral administration of CNTs at 10, and 50 mg/kg evoked a significant decrement in weight coefficient, sperm viability and motility, hypo-osmotic swelling (HOS) test, sperm count, mitochondrial dehydrogenase activity, ATP content, total antioxidant capacity, and GSH/GSSH ratio in the testis and epididymal spermatozoa. On the other hand, percent abnormal sperm, testicular and sperm TBARS contents, protein carbonylation, ROS formation, oxidized glutathione level, and sperm mitochondrial depolarization were considerably increased. Significant histopathological and stereological alterations in the testis occurred in the groups challenged with CNTs. The current findings indicated that oxidative stress and mitochondrial impairment might substantially impact CNTs-induced reproductive system injury and sperm toxicity. The results can also be used to establish environmental standards for CNT consumption by mammals, produce new chemicals for controlling the rodent populations, and develop therapeutic approaches against CNTs-associated reproductive anomalies in the males exposed daily to these nanoparticles.